2020
DOI: 10.1007/s12182-020-00526-x
|View full text |Cite
|
Sign up to set email alerts
|

Toward accurate density and interfacial tension modeling for carbon dioxide/water mixtures

Abstract: Phase behavior of carbon dioxide/water binary mixtures plays an important role in various CO2-based industry processes. This work aims to screen a thermodynamic model out of a number of promising candidate models to capture the vapor–liquid equilibria, liquid–liquid equilibria, and phase densities of CO2/H2O mixtures. A comprehensive analysis reveals that Peng–Robinson equation of state (PR EOS) (Peng and Robinson 1976), Twu α function (Twu et al. 1991), Huron–Vidal mixing rule (Huron and Vidal 1979), and Abud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 71 publications
(139 reference statements)
0
1
0
Order By: Relevance
“…They also proposed a new IFT correlation based on the PR EOS model, which improved consistency. The study showed the effectiveness of their models for CO 2 /H 2 O mixtures 30 . In their 2021 study, Roy Setiawan and co-researchers assessed various machine learning algorithms to predict the surface tension of binary mixtures containing ionic liquids.…”
Section: Introductionmentioning
confidence: 93%
“…They also proposed a new IFT correlation based on the PR EOS model, which improved consistency. The study showed the effectiveness of their models for CO 2 /H 2 O mixtures 30 . In their 2021 study, Roy Setiawan and co-researchers assessed various machine learning algorithms to predict the surface tension of binary mixtures containing ionic liquids.…”
Section: Introductionmentioning
confidence: 93%